2020
DOI: 10.1111/rda.13837
|View full text |Cite
|
Sign up to set email alerts
|

Follicle‐stimulating hormone and luteinizing hormone regulate the synthesis mechanism of dihydrotestosterone in sheep granulosa cells

Abstract: Steroid hormones and receptors play important roles in female reproduction, and their expression patterns affect follicular growth and development. To examine the expression of dihydrotestosterone (DHT) synthases (5α‐reductases (5α‐red1 and 5α‐red2)) and androgen receptor (AR) during follicular development, and the regulation of DHT signalling by follicle‐stimulating hormone (FSH) and luteinizing hormone (LH), we have used enzyme‐linked immunosorbent assays, quantitative real‐time polymerase chain reaction, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, through these cells, this hormone indirectly regulates spermatogonial stem cells (SSCs) and creates the adequate environment for germinative cells proliferation and differentiation [ 7 ]. Additionally, they regulate other physiological activities that have biological effects on the hypothalamus, pituitary, and reproductive organs [ 2 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, through these cells, this hormone indirectly regulates spermatogonial stem cells (SSCs) and creates the adequate environment for germinative cells proliferation and differentiation [ 7 ]. Additionally, they regulate other physiological activities that have biological effects on the hypothalamus, pituitary, and reproductive organs [ 2 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the changes in ovarian function were associated with changes in the hormone concentrations in the different photoperiods. As a cell survival factor [ 53 ] regulated by IGF-1, GnRH, and LH in the HPO axis, the FSH is crucial for inhibiting the granulosa cell apoptosis, promoting the follicle development [ 54 , 55 , 56 ], and regulating the ovarian development [ 57 , 58 , 59 ]. Here, compared with the MD group, the serum concentrations of IGF-1, GnRH, FSH, and LH were significantly lower in the SD group, but significantly higher in the LD group, indicating that the SD group promoted the granulosa cell apoptosis, whereas the LD group inhibited the granulosa cell apoptosis, as verified by the TUNEL assay.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental method was the same as that used in a previous study (Duan et al, 2021). A total of 26 sheep ovaries were used for this part.…”
Section: Methodsmentioning
confidence: 99%